Effect of Online Purchase - Seri Handayani; Zuhrinal M. Nawawi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The purpose of this research are to find out the effect of promotion on purchasing decisions in online stores and product quality's effect. The method used in this research is qualitative. Product quality is a product with ability to meet predetermined needs. Promotion is the activity of offering product to consumers. The purchasing decisions is a final result in buyer's determination. The result of this research shows that many people prefer to instead of shopping at offline stores.